Representations of fabric hand attributes in the cerebral cortices based on the Automated Anatomical Labeling atlas. Issue 18 (September 2019) - Wang, Qicai; Tao, Yuan; Zhang, Zhongwei; Yuan, Jie; Ding, Zuowei; Jiang, Zhaohui; Jia, Zhao; Wang, Jing
Fabric hand is most frequently used by consumers and researchers to evaluate the touch feeling of textiles. Academically, many methods have been developed to characterize it psychologically and physically, and the relationship between the hand attributes of fabrics and their physical properties are well understood. However, in physiological terms, the cognitive mechanism of the brain on different attributes of fabric hand is not clear. Previous studies have shown that the sensory or discrimination information from fabric touch can be detected by the technology of functional magnetic resonance imaging (fMRI). In this study, further fMRI experiments were carried out, attempting to find the relationship between the cerebral cortices of various brain areas and different hand attributes of fabrics. The subtle atlas of Automated Anatomical Labeling (AAL) was used to display and analyze the blood oxygenation level dependent signals completely and conveniently. The results showed that when the subjects touched two samples with distinct fabric hand in a specified way, activation information and the index of the mean signal in every related brain areas can distinguish them, and several brain regions in the AAL atlas are linked to different fabric hand attributes. The technology of fMRI was proved again to be a promising tool for studying the cognitive mechanism of the brain on fabric touch.